Identifying determinants of spatial agglomeration of healthcare resources by using spatial econometric methods: a longitudinal study in China - Dong, Enhong; Sun, Xiaoting; Xi, Yueming; Wang, Yijia; Wang, Tao; Gao, Weimin (Frontiers in Public Health, 2024)
Background: Health-care resources are necessary for individuals to maintain their health. The Chinese government has implemented policies to optimize the allocation of health-care resources and achieve the goal of equality in health care for the Chinese people since the implementation of the new medical reform in 2009. Given no study has investigated regional differences from the perspective of health-care resource agglomeration, the aim of this study was to investigate Chinas health-care agglomeration from 2009 to 2017 in mainland China and identified its determinants to provide theoretical evidence for the government to develop and implement scientific and rational health-care policies.The study was conducted using 2009-2017 data to analyze health-resource agglomeration on institutions, beds, and workforce in China. Agglomeration index was applied to evaluate the degree of regional differences in health-care resource allocation and spatial econometric models were constructed to identify determinants of spatial agglomeration of health-care resources.Results: From 2009 to 2017, all the agglomeration indexes of health care exhibited a downward trend except for the number of institutions in mainland China. Population density(PD), Government health expenditures(GHE), urban residents disposable income(URDI), geographical location(GL) and urbanization level(UL) all had positive significant effects on the agglomeration of beds, whereas both per capita health expenditures(PCHE), number of college students(NCS) and maternal mortality rate(MMR) had significant negative effects on the agglomeration of institutions, beds, and the workforce. In addition, population density(PD), per capita gross domestic product(PCGDP) in one province had negative spatial spillover effects on the agglomeration of beds and the workforce in neighboring provinces. However, MMR had a positive spatial spillover effect on the agglomeration of beds and the workforce in those regions.The agglomeration of health-care resources was observed to remain at an ideal level in overall mainland China from 2009 to 2017. According to the significant determinants, some corresponding targeted measures for Chinese government and other developing countries should be fully developed to balance regional disparities in the agglomeration of health-care resources across administrative regions.